In vitro and in vivo antimalarial activities of the ethanol extract of Erythrina sigmoidea stem bark used for the treatment of malaria in the Western Region of Cameroon - Jemimah Sandra, Tientcheu Noutong; Christelle Nadia, Noumedem Anangmo; Cedric, Yamssi; Guy-Armand, Gamago Nkadeu; Azizi, Mounvera Abdel; Aboubakar Sidiki, Ngouyamsa Nsapkain; Alex Kevin, Tako Djimefo; Payne, Vincent Khan; Hu, Haibo (Frontiers in Parasitology, 2024)
Background Malaria is one of the leading causes of morbidity and/or mortality in tropical Africa. The spread and development of resistance to chemical antimalarial drugs and the relatively high cost of the latter are problems associated with malaria control and are reasons to promote the use of plants to meet healthcare needs to treat malaria. The aim of this study was to evaluate antiplasmodial activities of extracts of Erythrina sigmoidea (Mah quat), which is traditionally used for the treatment of malaria in the western region of Cameroon. Material and methods The ethanol extract of E. sigmoidea stem bark was obtained through the maceration process using 95% ethanol, while the aqueous extract was prepared by infusion. The in vitro antiplasmodial effect of extracts against P. falciparum chloroquine-sensitive (3D7) and chloroquine-resistant (Dd2) strains was determined using the Trager and Jensen method. On the other hand, the in vivo antimalarial activity of the extract was evaluated in mice infected with Plasmodium berghei strain NK65 using the Peters’ 4-day suppressive test and Ryley test (curative test). A total of 36 mice were used, subdivided into six groups of six mice each: one normal control, a negative control, a positive control, and three other groups for the tested product. Blood samples were collected on the 10th day of each test for hematological parameters. Results The aqueous extract had an in vitro antiplasmodial activity against the chloroquine-sensitive strain with an IC50 of 29.51 ± 3.63 µg/mL and against the chloroquine-resistant strain with an IC50 of 35.23 ± 3.17 µg/mL. The highest in vitro antiplasmodial activity was observed with the ethanol extract against the chloroquine-sensitive strain with an IC50 of 6.44 ± 0.08 µg/mL and against the chloroquine-resistant strain with an IC50 of 7.53 ± 0.22 µg/mL. The ethanol extract demonstrated suppressive activity in vivo with reduction rates of 87.69%, 86.79%, and 81.08% at doses of 500 mg/kg, 250 mg/kg, and 125 mg/kg, respectively; and curative activity in vivo with reduction rates of 80%, 78.5%, and 77.5% at doses of 500 mg/kg, 250 mg/kg, and 125 mg/kg, respectively. The number of white blood cells in the negative control (44.55 ± 5.02 103/µL) was higher compared to the other groups. As for the red blood cells, we observed a massive destruction of the latter in the infected and untreated group (5.82 ± 1.50 106/µL) compared to the infected and ethanol extract-treated groups (8.74 ± 1.57 106/µL for 500 mg/kg, 7.54 ± 1.77 106/µL for 250 mg/kg, and 8.9 ± 1.50 106/µL for 125 mg/kg). Conclusion This study provides scientific data on the use of E. sigmoidea by the local population for the treatment of malaria. It shows that E. sigmoidea has antiplasmodial activity, and we also see that there are differences between the parameters that we have in the treated groups and those of the untreated group. However, toxicity tests are necessary to assess its safety.